Type 2 and other forms of diabetes in 0–30 year olds: a hospital based study in Leeds, UK. Issue 8 (22nd July 2003) - Feltbower, R G; McKinney, P A; Campbell, F M; Stephenson, C R; Bodansky, H J
Abstract : Background and Aims: Following recent reports of increased numbers of adolescents being diagnosed with the adult or type 2 form of diabetes we aimed to describe the prevalence of both type 2 and other forms of diabetes in an urban population of children and young people in northern England. Methods: A hospital based cross sectional study was performed in patients aged ≤30 years attending diabetic clinics in Leeds during the year 2000. Results: A total of 677 subjects were identified, of whom 621 (92%) and 37 (5%) had type 1 and type 2 diabetes respectively. Four patients had confirmed maturity onset diabetes of the young, while the cause was uncertain for four. Median age of all patients was 22 years, with 396 (58%) aged 20–30; 32/37 patients with type 2 diabetes were aged 20–30. The prevalence of type 2 diabetes was 0.13 per 1000 overall, compared to 2.2 per 1000 for patients with type 1 diabetes. Of all type 2 diabetes patients, 24% were south Asian compared to 5% of the background population; 87% were categorised into the two least affluent tertiles of the Townsend score. This link with deprivation was not explained by the proportion of Asian patients across tertiles (approximately 25%). Conclusions: This study shows extremely low prevalence of type 2 diabetes in 10–19 year olds, but will provide a baseline for future comparisons. Overall, type 2 diabetes is seen more commonly in south Asians, and an association with deprivation is suggested.